Comparative Evaluation Of Pediatric Dentifrices In Remineralizing Simulated Carious Lesions On Enamel: An In Vitro Approach - Chidambaram, Janani Vinodhini Nainer; Parthasarathy, Preethi; Kasi, Anand; Sujitha, P. (Journal of Neonatal Surgery, 2025)
Purpose: This study aimed to assess the remineralizing efficacy of three widely available pediatric dentifrices on artificially created carious lesions in primary teeth using high-resolution SEM-EDXA. Materials and methods: 30 decay-free primary teeth were demineralized for 96 hours and then cut into 30 sections longitudinally. The sections were randomly designated to three groups, each comprising 10 samples. Group A- Fluoridated dentifrice (KidsBunny), Group B- Non- Non-fluoridated dentifrice (MeeMee), Group C- Herbal dentifrice (MamaEarth). The samples were exposed to a 7-day pH cycle for remineralization and were then analyzed using SEM-EDXA. Results: The fluoridated dentifrice group showed a statistically significant increase in remineralizing potential. There was a varied difference in the remineralizing potential across all three groups. The herbal dentifrice group showed traces of added elements such as Iodine, Barium, and Silicon after remineralization. Conclusion: Fluoridated dentifrice (KidsBunny) showed increased remineralizing potential. Herbal dentrifice consisting of various extra elements that can prevent the tooth from acid erosion, oral infections, and aid in strengthening the enamel. Non-fluoridated dentrifice did not show remineralisation potential or elements being added post-remineralisation. Hence, different types of dentifrices can be prescribed to patients based on an individual’s food habits, diet pattern, and caries risk.